Septum Resection in Women With a Septate Uterus: A Cohort Study. Issue 2 (February 2021) - Rikken, J. F. W.; Verhorstert, K. W. J.; Emanuel, M. H.; Bongers, M. Y.; Spinder, T.; Kuchenbecker, W.; Jansen, F. W.; van der Steeg, J. W.; Janssen, C. A. H.; Kapiteijn, K.; Schols, W. A.; Torrenga, B.; et al.
Abstract : (Abstracted from Hum Reprod 2020;35(7):1578–1588) The septate uterus has an estimated prevalence of 0.2% to 2.3% in women of reproductive age and is associated with impaired reproductive outcomes, the biologic basis of which is unclear. The standard-of-care treatment for septate uterus is hysteroscopic septum resection.